A study on Malaysia atmospheric effect on radio over free space optic through radio frequency signal and light propagation in fiber for future communication development - Zainurin S.N.; Ismail I.; Saulaiman U.S.; Ismail W.Z.W.; Mustafa F.H.; Sahrim M.; Balakrishnan S.R.; Juliza Jamaludin (American Institute of Physics Inc., 2024)
Indexed by WOS/SCOPUS